Diabetes Prevalence Among Puerto Rican Adults in New York City, NY, 2000 - Melnik, Thomas A. (© American Journal of Public Health 2004, 2004)
This study assessed the prevalence of diagnosed diabetes and associated characteristics among Puerto Rican adults in New York City, NY, with a random-digit–dialed telephone survey with a dual-frame sampling design. Overall, 11.3% (95% confidence interval = 8.7%, 14.0%) had diagnosed diabetes; diabetes was significantly related to age, obesity, and family history; and the prevalence was high among those with the least education. This study showed the ability to obtain critically needed diabetes information from ethnic minorities at the local level.